Effects of task-based language teaching on speaking skills - Zainaba Omar; Norliza Jamaludin; Mahzan Arshad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Task-based language teaching (TBLT) has been widely researched and used in the teaching of languages since the 1980s. The objective of this study is to explore the effectiveness of TBLT in the teaching of speaking skills for primary school students in Singapore. Although this group of students are the native speakers of the Malay language, however, they are not only unable to speak the language fluently, but also have limited vocabulary. This study uses a quasi-experiment pre-post-test design for non-equivalent groups to determine whether there are any significant differences in the pre and post test scores for fluency, vocabulary, and language structure used among the treatment group. The score obtained is then compared with the control group which uses the conventional approach. The findings show that there are significant differences between the pre-test score and post-test score for the treatment group. There is no significant difference in the scores achieved by the control group. Hence, it is concluded that TBLT can be used to teach speaking skills to learners who need exposure to use the language. In general, the findings can be used by Malay teachers to add value to the teaching and learning of the Malay language in Singapore.